1998
DOI: 10.1007/s002239900467
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Content and Density in Professional Tennis Players

Abstract: Total and regional bone mineral content (BMC) as well as lean and fat mass were measured in nine male professional tennis players (TPs) and 17 nonactive subjects; dual-energy X-ray absorptiometry (DXA) was used for measuring. The mean (+/-SD) age, body mass, and height were 26 +/- 6 and 24 +/- 3 years, 77 +/- 10 and 74 +/- 9 kg, and 180 +/- 6 and 178 +/- 6 cm for the TP and the control group (CG), respectively. The whole body composition for BMC, lean mass, and fat of the TP was similar to that observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
131
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 33 publications
15
131
2
5
Order By: Relevance
“…25 Total and regional body composition was estimated by dual-energy X-ray absorptiometry (DXA) (Hologic QDR-1500, Hologic Corp., software version 7.10, Waltham, MA, USA) as described elsewhere. 26 The validity of DXA was established by comparison with chemical analysis in animals 27 and its reliability was illustrated by an intraclass correlation of 0.998 for repeated measurements of the percentage of body fat in children. 28 For the body composition determinations, it was assumed that the hydration of lean body mass is 73.2% and the percentage of fat in the brain 17.0%.…”
Section: Anthropometry and Body Compositionmentioning
confidence: 99%
“…25 Total and regional body composition was estimated by dual-energy X-ray absorptiometry (DXA) (Hologic QDR-1500, Hologic Corp., software version 7.10, Waltham, MA, USA) as described elsewhere. 26 The validity of DXA was established by comparison with chemical analysis in animals 27 and its reliability was illustrated by an intraclass correlation of 0.998 for repeated measurements of the percentage of body fat in children. 28 For the body composition determinations, it was assumed that the hydration of lean body mass is 73.2% and the percentage of fat in the brain 17.0%.…”
Section: Anthropometry and Body Compositionmentioning
confidence: 99%
“…30 Total and regional body composition was assessed by dualenergy x-ray absorptiometry (DXA) (Hologic QDR-1500, Hologic Corp., software version 7.10, Waltham, MA, USA) as described elsewhere. 31 Lean body mass (g), body fat (g) and BMC (g) were calculated from whole-body scans. Whole-body scans were submitted to a regional analysis to determine the composition of the arm, leg and trunk regions.…”
Section: Anthropometry and Body Compositionmentioning
confidence: 99%
“…With this analysis, regional body fat and lean mass can be assessed with a coefficient of variation below 5%. 31 Measurement of physical fitness Dynamic force and maximal isometric force. To assess the leg extension explosive strength, the jumping performance was measured in all children.…”
Section: Anthropometry and Body Compositionmentioning
confidence: 99%
“…Rehabilitation should take into account the fact that significant BMD changes were discovered with several different hip-site measurements. Calbet et al 4 found a significant increase in BMC in the dominant upper extremity of professional tennis players. While this demonstrates activity-specific increases in BMC, it is interesting to note that these changes were evidenced in an extremity that is predominantly nonweight bearing.…”
Section: Discussionmentioning
confidence: 95%